A Nanobody‐Conjugated DNA Nanoplatform for Targeted Platinum‐Drug Delivery. Issue 40 (27th August 2019) - Wu, Tiantian; Liu, Jianbing; Liu, Manman; Liu, Shaoli; Zhao, Shuai; Tian, Run; Wei, Dengshuai; Liu, Yangzhong; Zhao, Yao; Xiao, Haihua; Ding, Baoquan
Abstract: The targeted delivery of chemotherapeutic drugs is a major challenge in the clinical treatment of cancer. Herein, we constructed a multifunctional DNA nanoplatform as a versatile carrier of the highly potent platinum‐based DNA intercalator, 56MESS. In our rational design, 56MESS was efficiently loaded into the double‐bundle DNA tetrahedron through intercalation with the DNA duplex. With the integration of a nanobody that both targets and blocks epidermal growth factor receptor (EGFR), the DNA nanocarriers exhibit excellent selectivity for cells with elevated EGFR expression (a common biomarker related to tumor formation) and combined tumor therapy without obvious systemic toxicity. This DNA‐based platinum‐drug delivery system provides a promising strategy for the treatment of tumors. Abstract : A double‐bundle DNA tetrahedron‐based nanoplatform integrating a nanobody, which targets and blocks the epidermal growth factor receptor (EGFR), commonly overexpressed on the surface of tumor cells, and a platinum‐based DNA intercalator (56MESS) was constructed for efficient and targeted tumor therapy.